Dimensions of Instructor Disclosure: Implications for Rhetorical and Relational Goals of Instruction - Frisby, Brandi N (Communication research reports, 2017)
There are an array of reasons why instructors view personal disclosures as beneficial for the classroom, including to demonstrate caring and to make content relevant. Using the rhetorical and relational goals of instruction theory as the theoretical model, this study tested the potential for the three dimensions of disclosure (i.e., amount, negativity, relevance) to account for variance in instructor rhetorical goals (i.e., relevance) and relational goals (i.e., caring). The results highlight the importance of relevant instructor disclosures to perceiving an instructor as achieving rhetorical and relational goals within the classroom.
https://katalog.adlr.link/Record/ai-68-OLC1996370022